Patrimônio arquitetônico moderno: do debate às intervenções - Rocha, Mércia Parente (2011)
The recent debate on the conservation of modern heritage and the controversies raised in this regard have been, to some extent, fueled by the experiences of intervention in modern buildings, which have intensified in the last two decades. This paper examines the main issues raised by this debate, pointing to specifics, dilemmas and paradoxes related to the conservation of this architecture, its assumptions and its new status as historical patrimony, collated with some works of intervention carried out in this collection. It aims to understand how the issues related to conservation of this heritage are being resolved in practice, which means, to understand, from the works of interventions, how such architects are solving the dilemmas raised in the debate and what knowledge or theories are grounded.